Pelatihan Deteksi Dini Attention Deficit Hyperactivity Disorder (ADHD) pada Guru KB-TK Labschool Unesa - Yohana Wuri Satwika; Satiningsih; Siti Ina Savira; Miftakhul Jannah; Ira Darmawanti (Universitas Putra Indonesia YPTK Padang, 2022)
ADHD (Attention Deficit Hyperactivity Disorder) is a medical disorder that can be recognized by specific behavioral characteristics, namely inattention to surroundings, easily distracted condition, and an attitude of following one's own will. Children diagnosed with ADHD require special treatment so that their specificity can be fulfilled. Teacher knowledge about ADHD is an important thing in order to detect and provide the right educational model for students. The implementation of this training in community service uses modules and early detection tools for ADHD children or students. The purpose of this activity is so that teachers can identify the condition of their students whether any of these students lead to the characteristics of ADHD. Based on the results of the post-test and case discussions, the teachers at the beginning of the activity stated that they were still confused about the condition of their students so that they understood the situation of their students more clearly. The teachers also stated that they more clearly see the condition of the students they work with in class, especially for students who have a tendency to ADHD. ADHD (Atention Deficit Hiperactivity Disorder) adalah kelainan medis yang dapat dikenali dengan ciri-ciri perilaku khusus sikap kurang memperhatikan sekeliling, kondisi mudah terganggu, dan sikap mengikuti kemauannya sendiri. Anak yang terdeteksi ADHD membutuhkan penanganan yang khusus agar kekhususannya dapat terpenuhi. Pengetahuan guru tentang ADHD menjadi sebuah hal yang penting dalam rangka mendeteksi dan memberikan model pendidikan yang tepat bagi siswa. Pelaksanaan pelatihan dalam pengabdian kepada masyarakat ini ini menggunakan modul dan alat deteksi dini untuk anak/ siswa ADHD. Tujuan kegiatan ini adalah agar para guru dapat mengenali kondisi siswa mereka apakah ada dari para siswa tersebut yang mengarah kepada ciri-ciri ADHD. Berdasarkan hasil pre test post test dan diskusi kasus, para guru yang diawal kegiatan menyatakan masih bingung mengenai kondisi siswa mereka menjadi lebih memahami keadaan siswa mereka secara lebih jelas. Para guru juga menyatakan mereka lebih jelas melihat kondisi siswa yang mereka tangani di kelas terutama untuk siswa yang memiliki kecenderungan ADHD.